1992
DOI: 10.1016/0304-3959(92)90144-z
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-induced analgesia in chronic non-malignant pain: a meta-analysis of 39 placebo-controlled studies

Abstract: For 39 controlled studies on the analgesic effect of antidepressants, a meta-analysis was conducted to get an estimation of the effect size, and to obtain a sight on the possible modes of action and the methodology used. The mean size of the analgesic effect was 0.64. It means that the average chronic pain patient who received an antidepressant treatment had less pain than 74% of the chronic pain patients who received a placebo. This quantification, however, is only as good as the studies on which it is based,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
0
22

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(200 citation statements)
references
References 72 publications
2
176
0
22
Order By: Relevance
“…Firm evidence has shown that tricyclic antidepressants (TCAs) should be considered the gold standard treatment for neuropathic pain (Coluzzi and Mattia, 2005;Sindrup et al, 2005). It has also been reported that the analgesic effect of antidepressants is independent of their antidepressive action, and occurs at lower doses and with a faster onset of action in a clinical situation (Pilowsky et al, 1982;Onghena and Van Hondenhobe, 1992;Richeimer et al, 1997). This effect can be explained by several pharmacological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Firm evidence has shown that tricyclic antidepressants (TCAs) should be considered the gold standard treatment for neuropathic pain (Coluzzi and Mattia, 2005;Sindrup et al, 2005). It has also been reported that the analgesic effect of antidepressants is independent of their antidepressive action, and occurs at lower doses and with a faster onset of action in a clinical situation (Pilowsky et al, 1982;Onghena and Van Hondenhobe, 1992;Richeimer et al, 1997). This effect can be explained by several pharmacological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors have proposed that SSRIs may enhance the process underlying acute pain (Dirksen R, 1998). A meta-analysis of antidepressant-induced analgesia by Onghena and colleagues found that selective NRIs were no more efficacious than dualaction antidepressants (Onghena & Van Houdenhove, 1992). However, based on the evidence described here, we can conclude that drugs that inhibit the reuptake of monoamines are likely to be effective in the treatment of chronic pain.…”
Section: Clinical Studiesmentioning
confidence: 59%
“…Several studies have demonstrated the intrinsic analgesic effects of antidepressants (McQuay et al, 1996;Onghena & Van Houdenhove, 1992;Smith et al, 1998). However, it remains unclear whether antidepressants are efficacious for the treatment of all types of pain or only for specific subtypes.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…It was estimated that tricyclic antidepressants are effective in the model of neuropathic pain evoked by ligation of the sciatic nerve in rats [39]. Currently it is under consideration that antidepressant drugs act not only as mood elevators but also analgesics in chronic pain syndromes [40]. The antidepressant amitriptyline is used as an adjuvant in the treatment of a variety of chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%